THE EFFECT OF CORPORATE GOVERNANCE MECHANISMS ON DEBT POLICY: EVIDENCE FROM INDONESIA’S CONSUMER NON-CYCLICAL COMPANIES - Muhammad Gifari; Aloysius Harry Mukti; Wijaya Triwacananingrum (Universitas Airlangga, 2025)
This study examines the influence of good corporate governance mechanisms specifically institutional ownership and managerial ownership on debt policy in non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2021. The research addresses a gap in previous studies that have shown inconsistent findings regarding the relationship between ownership structure and debt policy in emerging markets. Using a purposive sampling method, 217 firm-year observations were analyzed through linear regression analysis. The empirical results reveal that both institutional ownership and managerial ownership have no significant effect on debt policy, indicating that ownership structures do not play a dominant role in determining financing decisions. However, liquidity (measured by the current ratio) and firm size are found to have a positive and significant effect on debt policy, suggesting that companies with higher liquidity levels and larger firm sizes tend to utilize more debt in their capital structure. These findings contribute to the understanding of how corporate governance and firm characteristics influence debt financing behavior in Indonesia’s non-cyclical consumer sector and offer practical implications for policymakers, investors, and corporate managers in enhancing governance and financial decisionmaking practices.